Comparison of rhinitis treatments using MASK-air® data and considering the minimal important difference - Sousa-Pinto, Bernardo; Schünemann, Holger J; Sá-Sousa, Ana; Vieira, Rafael José; Amaral, Rita; Anto, Josep M; Klimek, Ludger; Czarlewski, Wienczyslawa; Mullol, Joaquim; Pfaar, Oliver; Bedbrook, Anna; Brussino, Luisa; et al. (Allergy, 2022)
BACKGROUND: Different treatments exist for allergic rhinitis (AR), including pharmacotherapy and allergen immunotherapy (AIT), but they have not been compared using direct patient data (i.e., "real-world data"). We aimed to compare AR pharmacological treatments on (i) daily symptoms, (ii) frequency of use in co-medication, (iii) visual analogue scales (VASs) on allergy symptom control considering the minimal important difference (MID) and (iv) the effect of AIT. METHODS: We assessed the MASK-air® app data (May 2015-December 2020) by users self-reporting AR (16-90 years). We compared eight AR medication schemes on reported VAS of allergy symptoms, clustering data by the patient and controlling for confounding factors. We compared (i) allergy symptoms between patients with and without AIT and (ii) different drug classes used in co-medication. RESULTS: We analysed 269,837 days from 10,860 users. Most days (52.7%) involved medication use. Median VAS levels were significantly higher in co-medication than in monotherapy (including the fixed combination azelastine-fluticasone) schemes. In adjusted models, azelastine-fluticasone was associated with lower average VAS global allergy symptoms than all other medication schemes, while the contrary was observed for oral corticosteroids. AIT was associated with a decrease in allergy symptoms in some medication schemes. A difference larger than the MID compared to no treatment was observed for oral steroids. Azelastine-fluticasone was the drug class with the lowest chance of being used in co-medication (adjusted OR = 0.75; 95% CI = 0.71-0.80). CONCLUSION: Median VAS levels were higher in co-medication than in monotherapy. Patients with more severe symptoms report a higher treatment, which is currently not reflected in guidelines.
Keywords: Rhinitis; rýma; Rhinitis, Allergic; Desensitization, Immunologic; lidé; Fluticasone; Adrenal Cortex Hormones; hormony kůry nadledvin; Humans; desenzibilizace imunologická; alergická rýma; flutikason